THE ROLE OF LOCAL GOVERNMENTS IN THE PROTECTION OF SUSTAINABLE AGRICULTURAL LAND IN BONTOA DISTRICT, MAROS REGENCY - Pombo, Nurul Afifah; Aslinda, Andi; Halim, Didin (Universitas Negeri Makassar, 2025)
This research aims to determine the Role of Local Government in Protecting Sustainable Agricultural Land in Bontoa District, Maros Regency. This research is a qualitative descriptive study. Data collection was carried out using observation, interview and documentation techniques. The data analysis techniques used consist of data collection, data reduction, data display, verification and validation. The research results show that the role of the Regional Government in Protecting Sustainable Agricultural Land in Bontoa District, Maros Regency is in the less effective category. Looking at the research focus, namely: 1) regulators in the poor category; 2) the dynamizer is in the poor category; 3) the facilitator is in the good category; 4) the catalyst is in the poor category